1997
DOI: 10.1097/00005768-199707000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Improved running performance in hot humid conditions following whole body precooling

Abstract: On two separate occasions, eight subjects controlled speed to run the greatest distance possible in 30 min in a hot, humid environment (ambient temperature 32 degrees C, relative humidity 60%). For the experimental test (precooling), exercise was preceeded by cold-water immersion. Precooling increased the distance run by 304 +/- 166 m (P < 0.05). Precooling decreased the pre-exercise rectal and mean skin temperature by 0.7 degrees C and 5.9 degrees C, respectively (P < 0.05). Rectal and mean skin temperature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
154
3
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(177 citation statements)
references
References 28 publications
18
154
3
2
Order By: Relevance
“…In female subjects, the number of erythrocytes decreased from 4.58 to 4.45 million/mm 3 after the treatments. Significant (P < 0.05) decreases body cooling before endurance exercise allows for a greater thermal stress during prolonged work of submaximal intensity [30,34]. The research presented here indicates a significant increase in anaerobic power as a consequence of ten sessions of the whole body cryostimulation, particularly in male subjects.…”
Section: O R I G I N a L P A P E R S Ijomeh 2010;23(2)mentioning
confidence: 56%
See 1 more Smart Citation
“…In female subjects, the number of erythrocytes decreased from 4.58 to 4.45 million/mm 3 after the treatments. Significant (P < 0.05) decreases body cooling before endurance exercise allows for a greater thermal stress during prolonged work of submaximal intensity [30,34]. The research presented here indicates a significant increase in anaerobic power as a consequence of ten sessions of the whole body cryostimulation, particularly in male subjects.…”
Section: O R I G I N a L P A P E R S Ijomeh 2010;23(2)mentioning
confidence: 56%
“…Most researchers have addressed the effects of local cold treatments, where particular parts of the body were cooled or whole body was immersed in cold water on the level of chosen motor abilities or physical work capacity, under different temperatures [30][31][32][33][34][35][36]. Others evaluated the influence of cooling on the rate of recovery following injuries [19,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pre-cooling may delay the onset of fatigue by increasing time to exhaustion in temperate conditions, when working at either fixed 66) or self-selected rates 32) . This benefit has subsequently been extended to include hot environments 11,13,27) . Recently, we have undertaken a series of pre-cooling experiments, using the whole-body immersion method to pre-cool subjects prior to exercise in the heat 12,13,47) .…”
Section: Pre-coolingmentioning
confidence: 99%
“…For example previous studies have shown that lowering body temperature by either cooling with ice packs or lowering ambient temperature will improve exercise performance (3,10,12). There have however been no studies that have examined neuromuscular activity in these circumstances (20).…”
Section: Introductionmentioning
confidence: 99%